METHODOLOGY OF COSEISMIC DISPLACEMENTS COMBINATION OBTAINED BY DATA STEMMING FROM HETEROGENEOUS GEODETIC NETWORKS: ON THE EXAMPLE OF THE GREAT 2011 TOHOKU EARTHQUAKE, Mw 9.1 - N. V. Shestakov; М. D. Gerasimenko; А. К. Kishkina; V. G. Bykov; V. V. Pupatenko; А. S. Prytkov; N. F. Vasilenko; V. S. Zhizherin; S. V. Yakovenko (Геодинамика и тектонофизика)
The strongest earthquakes with magnitudes Mw 8–9 generate coseismic displacements of the Earth’s crust, covering entire regions of the world. These displacements can be recorded using observations provided by the independent geodetic GNSS networks. The data of these networks are processed using different algorithms and methods for analyzing satellite observations, methods for calculating the coseismic shift, and different implementations of the coordinate system. These factors lead to "inconsistency" of the combined displacement fields and the appearance of additional errors in the results of coseismic effects modeling. The paper proposes a method for combining the fields of coseismic displacements of the Earth's crust, obtained in the far-field zone from the source according to data from heterogeneous GNSS networks. The results of applying the proposed method are demonstrated by the example of combining the fields of coseismic displacements in China, South Korea and the south of the Far East of the Russian Federation, initiated by the catastrophic Tohoku earthquake on March 11, 2011, Mw 9.1, as well as the calculation and analysis of the unified field of coseismic deformations of the region under study.